(untitled) - Krylov, V. I. (Moskva, 1977)
Contents: Part 1 Inversion of the laplace transfofmation; Chapter one: Introduction; Chapter 2. Some analytical Methods for computing inverse laplace transforms; Chapte 3. Methods of numerical inversion of laplace transforms based on the use of special expansions
Keywords: Fourier transformations,Phép biến đổi Fourier,Phép biến đổi Laplace,Laplace transformation